Evaluation of a tumor detection microwave system with a realistic breast phantom. Issue 1 (January 2017) - Koutsoupidou, Maria; Karanasiou, Irene S.; Kakoyiannis, Constantine G.; Groumpas, Evangelos; Conessa, Christophe; Joachimowicz, Nadine; Duchêne, Bernard
ABSTRACT: In this article, we describe recent advances regarding a novel microwave imaging system intended to be used for in‐depth inspection of breast tissues. The system is made of a circular five‐element antenna array surrounding the breast that can be moved axially to perform a scan of the entire breast. The performance of the system is studied, both numerically and experimentally with a realistic anthropomorphic breast phantom, as a proof of concept of its fast and accurate screening ability to detect tumor‐like inclusions. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:6–10, 2017